Gold as a Safe Haven During the 2025 Global Tax War: A Qualitative Literature Review - Hengki Mangiring Parulian Simarmata; Poltak Pardamean Simarmata; Jusra Tampubolon (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2025)
This study investigates the strategic role of gold as a haven asset amid the anticipated 2025 global tax war, characterised by rising fiscal protectionism, currency volatility, and geopolitical fragmentation. Employing a qualitative literature review, the research synthesises scholarly findings, institutional data, and financial commentary to examine how gold performs under fiscal-driven crises. The findings reveal that gold remains a reliable hedge against inflation, exchange rate risk, and systemic policy shocks, supported by strong institutional trust and long-term investor demand. However, most prior studies focus on financial or monetary crises, leaving a significant gap in understanding gold's behaviour during state-led fiscal confrontations. This paper contributes by framing gold's relevance through a multi-dimensional lens, incorporating macroeconomic policy, digital investment behaviour, and central bank strategy. Further research is recommended to explore the impact of digital gold adoption in emerging markets and its implications for retail investor behaviour.